Transparency Change Mechanochromism Based on a Robust PDMS‐Hydrogel Bilayer Structure. Issue 1 (27th October 2020) - Xu, Yonghang; Zeng, Songshan; Xian, Weikang; Lin, Limiao; Ding, Hao; Liu, Jingjing; Xiao, Min; Wang, Shuanjin; Li, Ying; Meng, Yuezhong; Sun, Luyi
Abstract: Hydrogels and polydimethylsiloxane (PDMS) are complementary to each other, since the hydrophobic PDMS provides a more stable and rigid substrate, while the water‐rich hydrogel possesses remarkable hydrophilicity, biocompatibility, and similarity to biological tissues. Herein a transparent and stretchable covalently bonded PDMS‐hydrogel bilayer (PHB) structure is prepared via in situ free radical copolymerization of acrylamide and allylamine‐exfoliated‐ZrP (AA‐e‐ZrP) on a functionalized PDMS surface. The AA‐e‐ZrP serves as cross‐linking nano‐patches in the polymer gel network. The covalently bonded structure is constructed through the addition reaction of vinyl groups of PDMS surface and monomers, obtaining a strong interfacial adhesion between the PDMS and the hydrogel. A mechanical‐responsive wrinkle surface, which exhibs transparency change mechanochromism, is created via introducing a cross‐linked polyvinyl alcohol film atop the PHB structure. A finite element model is implemented to simulate the wrinkle formation process. The implication of the present finding for the interfacial design of the PHB and PDMS‐hydrogel‐PVA trilayer (PHPT) structures is discussed. Abstract : A mechanical‐responsive wrinkle surface, exhibiting transparency change mechanochromism, is created on a robust PDMS‐hydrogel bilayer structure.